Hybridity In Eschatological Belief Among Indonesian (Javanese) Catholics - Amadea Prajna Putra Mahardika (Fakultas Teologi, Universitas Sanata Dharma, 2025)
Indonesia, with its vast religious and cultural diversity, presents a unique religious dynamic, especially for Catholics in Java. The influence of local traditions and interfaith interactions often lead to multiple religious belonging, where Catholic believers integrate local spiritual elements into their eschatological beliefs. This hybridity manifests in practices such as ancestral rituals, the adaptation of Javanese symbols, and the blending of indigenous eschatological concepts with Catholic doctrine. This paper explores how the phenomenon of multiple religious belonging influences the eschatological understanding of Javanese Catholics and how hybridity facilitates dialogue between faith and local traditions. The study also examines the theological implications of this hybridity, assessing its impact on Catholic doctrinal integrity and its potential to enrich spiritual practices. Ultimately, this research aims to provide insights for the Catholic Church in guiding its followers through cultural and religious pluralism.